The relationship between trait mindfulness and subjective wellbeing of kindergarten teachers: The sequential mediating role of emotional intelligence and self-efficacy - Pan, Baocheng; Fan, Shiyi; Wang, Youli; Li, You (Frontiers in Psychology, 2022)
This study explored the relationship between emotional intelligence and self-efficacy in trait mindfulness and subjective wellbeing. In this study, 323 Chinese kindergarten teachers were measured using the Five Facet Mindfulness Questionnaire, Emotional Intelligence Scale, General Self-efficacy Scale, and Subjective Wellbeing Scale. The study found that subjective wellbeing can be predicted directly from trait mindfulness (β = 0.257, p < 0.001). Emotional intelligence could mediate the relationship between trait mindfulness and subjective wellbeing (β = 0.165, p = 0.006). Self-efficacy could mediate the relationship between trait mindfulness and subjective wellbeing (β = 0.078, p = 0.032). In addition, emotional intelligence and self-efficacy played a sequential mediating role between trait mindfulness and subjective wellbeing (β = 0.072, p = 0.005). This study revealed the relationship between kindergarten teachers’ trait mindfulness and subjective wellbeing through structural equation modeling and understood its role path, enriching the research on the Chinese preschool teachers in the field, and providing a literature reference for the international community to understand the Chinese kindergarten teachers. At the same time, the study also has some limitations, such as the use of a cross-sectional design method, a relatively single method, and the impact of COVID-19. However, we believe that this study will further enrich the research literature on the relationship between trait mindfulness and subjective wellbeing of Chinese kindergarten teachers.